The games in the correction of hyperactivity in children in the community - Jenny Nariño-Cuello (Universidad de Guantánamo, 2015)
Games are nowadays for the contemporary Physical Education one of the fundamental means for the pupils' physical and educational formation. A diagnosis made resulted in the scientific problem: How do we contribute through the games at the lessons of Physical Education to the correction of manifestations of hyperactivity? The study was conducted at the Elementary School 23 de Agosto of Guantánamo municipality. As objective of investigation we propose a set of didactic games for the correction of manifestations of hyperactivity in pupils of the second grade. To achieve accurate diagnosis different scientific methods were used: logical, documentary analysis and the system focus. The theoretic contribution is the establishment of psycho-pedagogical characteristics of children with manifestations of hyperactivity; on the other hand the paper contributes a set of methodological suggestions that can be used by the professors of Physical Education in the process of teaching and learning.